Aquatic Macroinvertebrate Community Changes Downstream of the Hydropower Generating Dams in Myanmar-Potential Negative Impacts From Increased Power Generation - Ko, Nyein Thandar; Suter, Phil; Conallin, John; Rutten, Martine; Bogaard, Thom (Frontiers in Water, 2020)
Intensive and incessant disruptions in watercourses such as dams are taking place due to the growing demand for hydroelectric generation, and can result in severe deterioration of ecosystem integrity. This research concentrates on the impact of dams on macroinvertebrate communities downstream of two hydropower dams on tributaries of the upper Ayeyarwady River basin (Myitnge and Chaungmagyi Rivers) in Myanmar. A total of 52 and 49 aquatic invertebrate taxa with a total abundance of 2743 and 1356 were collected from the Myitnge and Chuangamgyi Rivers respectively. We found the natural flow regime changed in both study rivers after the construction of the dams. Consequently, the communities of morphospecies of taxa and the very sensitive insects (Ephemeroptera, Plecoptera, Trichoptera, and Odonata, EPTO) were significantly different between upstream and downstream of both dams. We used the preliminary Myanmar Aquatic Biomonitoring Assessment Index to detect ecological water quality. The results of the index using all taxa at family-level showed that the ecological water quality indices upstream of the dams were better than those indices downstream of the dams. Our research showed that macroinvertebrates communities can be used as a bioindicator to detect the impact of human influences on river health such as dams. We concluded that the novel biomonitoring assessment tool recently developed for Myanmar is a promising monitoring tool as further river development occurs in Myanmar, which could also be linked to citizen science projects.